Upper Bound Limit Analysis of 2D Structures Using Lagrange Extraction-Based Isogeometric Analysis - Do, Van Hien (Journal of Technical Education Science, 2023)
This work presents a new approach that uses Lagrange extraction-based isogeometric analysis and Second Order Cone Programming (SOCP) to determine the limit load factor in two-dimensional problems. This methodology makes use of an upper-bound limit approach and a rigid-perfectly plastic material model. Lagrange extraction is used to link a C0 nodal basis to a smooth B-spline basis. This enables the use of straightforward methods for isogeometric analysis in conventional finite element systems. A SOCP problem is created from the limit analysis problem, which may then be solved using Mosek optimization software. The numerical results indicate the correctness and effectiveness of the current technique by contrasting it with other approaches mentioned in the literature.